2009
DOI: 10.1186/ar2591
|View full text |Cite
|
Sign up to set email alerts
|

Women, men, and rheumatoid arthritis: analyses of disease activity, disease characteristics, and treatments in the QUEST-RA Study

Abstract: IntroductionGender as a predictor of outcomes of rheumatoid arthritis (RA) has evoked considerable interest over the decades. Historically, there is no consensus whether RA is worse in females or males. Recent reports suggest that females are less likely than males to achieve remission. Therefore, we aimed to study possible associations of gender and disease activity, disease characteristics, and treatments of RA in a large multinational cross-sectional cohort of patients with RA called Quantitative Standard M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
4
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(108 citation statements)
references
References 58 publications
8
95
4
1
Order By: Relevance
“…Both in patients and animal models of SLE, studies have shown that the activation of FccRI/ CD64 is pivotal to the development of systemic inflammation and renal diseases [21,22]. However, in our study, no significant difference in expression levels of activating FccRI/CD64 expression was found between HT patients and healthy donors.…”
Section: Discussioncontrasting
confidence: 79%
“…Both in patients and animal models of SLE, studies have shown that the activation of FccRI/ CD64 is pivotal to the development of systemic inflammation and renal diseases [21,22]. However, in our study, no significant difference in expression levels of activating FccRI/CD64 expression was found between HT patients and healthy donors.…”
Section: Discussioncontrasting
confidence: 79%
“…In the latter an incidence peak is notable following menopause. Furthermore, FcR expressions are affected by states of chronic inflammation (33,34) and immunosuppressive therapies, such as steroids or methotrexate (35,36). These drugs are often used to treat both psoriasis and PsA.…”
Section: Discussionmentioning
confidence: 99%
“…[59][60][61] It is also known that 80% of people with RA are female. 6,59 Previous studies that assessed the effects of ICI in people with RA 49,58 and OA 17,36 also reported greater recruitment of female participants. However, because the reports of these studies did not separate results by gender, we are unable to determine whether the effects of ICI on lower-limb kine- matics and spatiotemporal parameters of gait are consistent across genders or whether gender affects these measurements in people with RA of the knee.…”
Section: Limitationsmentioning
confidence: 98%